A history of India - Kulke, Hermann; Rothermund, Dietmar (Routledge, Taylor & Francis Group, 2016)
"Covers the major political, economic, social and cultural forces that have shaped the history of the Indian subcontinent"--Provided by the publisher
Includes bibliographical references and index
Keywords: India -- History -- India -- History; Geschichte Anfänge-2014; Indien